Design and Build a Push-Pull Inverter for Room Lighting - Haryanti, Munnik; Yulianti, Bekti; Rahmawati, Cynthia; Adhicandra, Iwan (Tecno Scientifica Publishing, 2025)
This study addressed the issue of harmonic distortion in solar power systems that required inverters to convert DC voltage to AC for indoor lighting applications. The objective was to design and evaluate a push-pull inverter incorporating pulse width modulation (PWM) to reduce harmonics and ensure a stable voltage output. A push-pull topology was selected because of its relatively simple design and ability to step up DC voltage using a transformer, making it suitable for low- to medium-power applications. The inverter employed two metal–oxide–semiconductor field-effect transistor (MOSFET) switching devices operated alternately to generate AC waves at the output. The core of the design was a 50 Hz pulse generator producing a 5 V pulse signal with a small current, which was then amplified using a current amplifier before being supplied to the transformer. The transformer functioned to induce the electromagnetic field from the pulse source and release it at a higher voltage of 220 V. Experimental testing was performed using 2.3 W, 5 W, and 8 W LED lights. A minor modification to the gate resistor improved system performance, resulting in stable transformer output voltages at 5 W and 8 W loads. These results demonstrated that the PWM-controlled push-pull inverter successfully reduced harmonics and maintained voltage stability under higher loads, making it effective for indoor LED lighting powered by solar energy. Future studies could aim to enhance efficiency at lower loads, minimize switching losses, and implement more advanced PWM techniques to achieve performance levels comparable to pure sine wave inverters.